The Closing of the Muslim Mind: How Intellectual Suicide Created the Modern Islamist Crisis by Robert R. Reilly (Wilmington, DE: ISI Books, 2010. hbk. 244 pages.) (American Journal of Islam and Society, 2011)
This book looks like a serious academic study in Islamic theology. Itis divided into nine chapters that build on an overall argument andhas a great number of endnotes, quoting Muslim sources and literaturepro-duced in the field of Islamic studies. The book’s author workswith-in Washington’s circle of government institutions and thinktanks. His book comes with a foreword and no fewer than tenendorsements by colleagues of Reilly, which praise his erudition,insight, and abil-ity to analyze and explain the Muslim mind. Iwonder whether they were all aware that the book they endorsed is, in fact, a Catholic refutationof Ashʿarite Muslim theology, the leading branch of Sunni theology.However, Reilly exempts Shiite theology from his harsh criticism ...